Dynamics of heat and moisture transfer in wooden structures tied with metallic fasteners. Issue 1 (2nd January 2020) - Fedosov, Sergey; Kotlov, Vitaliy
Abstract: The article confers the influence of cyclically varying temperature and humidity of the environment on the behavior of wooden truss structures with metallic fasteners. The purpose of this work was to establish a mathematical model for the dynamics of temperature and humidity fields in the wood with metallic joints that accounts for changes in the environmental parameters, such as temperature and humidity, as well as to perform experimental study of the heat and mass transfer processes in wooden structures. The boundary problems of heat and moisture transfer in the components of wooden structures tied with dowels are formulated and analytically solved using the method of integral Laplace transform. The results of experimental studies on the processes of heat and moisture transfer through the components of wood truss structures are presented as graphs for temperature and humidity distribution in the dowel joints of wooden structures. The results of this study open up prospects for further research and development of recommendations for monitoring the condition of the components of wooden truss structures.